Fungsi Pancasila Sebagai Benteng Keberagaman Negara Kesatuan Republik Indonesia - Kalfin Febrian Nababan; Soca Ahmad (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
ABSTRACT Pancasila, as the foundation of the Indonesian state, plays a central role in maintaining diversity in the Unitary State of the Republic of Indonesia (NKRI). In the context of rich multiculturalism, Pancasila functions as a philosophical and moral foundation that binds the Indonesian nation. This abstract explores the role of Pancasila as a fortress that ensures unity in the ethnic, cultural, religious and linguistic diversity that exists in Indonesia. Pancasila affirms the principles of unity, social justice, democracy and just and civilized humanity, creating a framework that allows Indonesian people to live side by side in harmony. By understanding and internalizing the values ​​of Pancasila, Indonesian people can strengthen the country's sovereignty and build a strong foundation for an inclusive and sustainable future.